Gender and solid waste management in South African local government: a reflective analysis of policy and legislation - SIKHOSANA, Nqobile (Journal of Social Sciences)
This article examines the extent to which gender dimensions have been entrenched within solid waste management in the South African local government context. The main rationale for the study is that solid waste management policies, legislation and regulations have been crafted in a way that emphasises technical trash disposal, with little or no consideration devoted to the social and economic aspects in households. The findings of a comprehensive examination into how gender influences solid waste management and the relevance of this in tackling service delivery are discussed in this paper. The paper and its supporting research are informed by an ecofeminist approach that claims that gender equality is required for effective management of the environment. Using a qualitative literature review as the basis for research method, findings reveal that numerous policies and regulations exist. The concept of gender remains at the periphery of solid waste management and has not been fully incorporated into policy design. The study recommends a revision of such frameworks to ensure that gender specifics are detailed and guide local governments in mainstreaming gender in solid waste management.